ANALSISI PENGELOLAAN RISIKO PADA BUDIDAYA TAMBAK UDANG VANAME DI KECAMATAN MUARA BATU KABUPATEN ACEH UTARA - Nurul Febriani Siregar; Sakral Hasby Puarada; Nopri Yanto; Hafni Zahara; Muhammad Authar ND (Jurnal Mahasiswa Agribisnis, 2025)
This research is motivated by an analysis of risk management in vaname shrimp pond cultivation in Muara Batu District, North Aceh Regency. The problems faced by vaname shrimp farmers are caused by several risk factors resulting in changes in production, therefore it is necessary to carry out a risk management analysis in vaname shrimp farming. This research aims to analyze the risks of vaname shrimp pond cultivation in Muara Batu District, North Aceh Regency and to identify strategies that can be implemented to overcome the risks of vaname shrimp pond cultivation in Muara Batu District, North Aceh Regency. The sampling method is carried out by census or saturated side technique from the total population of pond farmers who have a minimum pond area of 10.000 m2. The total population taken was 20 respondents. The type of data used in this research uses primary data and secondary data. The data analysis method used in this research is a quantitative descriptive method which is measured using z - score analysis to calculate risk probability, and VaR analysis to measure the impact caused. The results of this research show that the source of risk identified is that the risk source for fry has the highest probability, namely 9,1% with a loss impact of IDR 416.540 and a risk status of 3.790.514, a feed probability of 8.3% with a loss impact of IDR 195.433 and a risk status amounting to 1.563.464 and a human resource probability of 7%, with a loss impact of Rp. 135.006 and a risk status of 945.042. The source of risk in quadrant II is fry and feed, in quadrant III the source of risk is labor. The strategies used to handle risk sources are preventive strategies and mitigation strategies. Keywords: Risk, Vaname Shrimp, z - score, VaR, Preventive Strategy, Mitigation Strategy.